Marginal Leakage of Class V Composite Resin Restorations - Maryam Khoroushi; Shahab Etemadi; Mitra Karbasi Kheir (Wolters Kluwer Medknow Publications, 2018)
>Introduction: Marginal leakage is one of the significant causes of restoration failure. This in-vitro study was conducted to compare cone beam computed tomography (CBCT) and dye-penetration methods for determining marginal leakage at gingival surface of class V resin composite restorations.Materials and Methods: Class V cavities were prepared on the buccal surfaces of nineteen caries-free extracted human molar teeth. Cavities were conditioned and filled. The teeth were immersed in a 50% w/w aqueous silver nitrate solution for 24 h and were taken out and rinsed with distilled water. Then, they were put into a developing solution. Whole specimens were first viewed with CBCT and were then sectioned and evaluated by stereomicroscope.Results: Measurement of agreement between CBCT and stereomicroscope revealed that 15 (78.9%) teeth had score 0, 1 (5.3%) tooth had score 1, and 1 (5.3%) tooth had score 2 in both techniques. Measurement of agreement between CBCT and stereomicroscope techniques, in the detection of marginal leakage, was 89.5% (Kappa coefficient = 0.627, P = 0.00). The Wilcoxon paired rank test revealed no significant difference between the results of CBCT and stereomicroscope in measuring the leakage at gingival margin (P = 0.157).Conclusion: Considering the limitations of the study, there was no significant difference between the results of CBCT and stereomicroscope in measuring the leakage at gingival margin of class V composite restorations. CBCT can be used noninvasively to detect the marginal leakage of gingival wall of class V composite restorations using aqueous silver nitrate solution as a tracer.